A systematic review of antipsychotic agents for primary delusional infestation. (17th February 2022) - McPhie, Meghan L.; Kirchhof, Mark G.
Abstract: Background: Delusional infestation (DI) is a rare delusional disorder in which individuals have a false belief that they are infested with bugs, parasites, or insects, despite the lack of medical evidence that such an infestation exists. Data on the effectiveness of antipsychotics for DI are limited. Methods: We conducted a systematic review using EMBASE, MEDLINE, PsycINFO, and Cochrane Central Register of Controlled Trials from inception of the databases up until July 20, 2018. Studies examining typical or atypical antipsychotics for primary DI were included. Results: A total of 51 relevant articles were identified, primarily case reports/series. Overall response was favorable for both typical and atypical antipsychotics, but there was no strong evidence to suggest that any one antipsychotic agent was preferable to other agents. Pimozide (1–16 mg/day) and risperidone (0.5–8 mg/day) were the most commonly studied typical and atypical antipsychotics, respectively. Inconsistent reporting of treatment outcomes and variability in study designs limited the overall evaluation of the data. Conclusions: There remains a lack of sound data supporting the effectiveness of antipsychotic treatment for primary DI. Further research is required to establish more definitive conclusions about the relative clinical utility of antipsychotic agents for DI.